Residual stress analysis of diamond‐coated WC–Co cutting tools: separation of film and substrate information by grazing X‐ray diffraction. (25th September 2013) - Meixner, M.; Klaus, M.; Genzel, Ch.; Reimers, W.
<x xml:space="preserve">Abstract</x> Chemical vapour deposition (CVD) of diamond surface layers is an effective way of improving the properties of cemented carbide cutting tools. Inadequate coating adhesion is one of the main issues and it may be affected by the residual stresses of the CVD diamond films. The most common methods for nondestructive residual stress analysis are based on X‐ray diffraction. The present paper deals with the particular case of determining the residual stress state of thin CVD diamond layers deposited on cobalt cemented tungsten carbide (WC–Co) substrates. It will be shown that the application of the conventional sin2ψ method might lead to erroneous results, as a result of superimposing diffraction lines originating from cobalt and the diamond coating. An approach to separating information on the substrate and film, based on grazing conditions in the symmetrical Ψ mode of diffraction, is presented. The results, revealing large compressive stresses within the coating, are compared with those obtained by supplementary micro‐Raman spectroscopy investigations.